Efficiency of land resources use by agricultural enterprises of Zhytomyr region - Karas, I.; Kotkova, T. (Land Management, Cadastre and Land Monitoring, 2019)
Ukraine belongs to agricultural states and has high percent of plowed land. The same tendency is typical for Zhytomyr region, on territory of which more than 350 thousand hectares of highly fertile soils are allocated. However, high land plowing and the favorable raw material base do not always indicate the high economic development of agriculture of the administrative-territorial formation. The task of our research was to analyze the development of crop and livestock production, their share in the structure of agricultural products, as well as the level of population provision by these products in Zhytomyr region.The establishment of the efficiency of the land resources use in the studied region was carried out by statistical analysis.Crop production in Zhytomyr region is represented mainly by the following crops: cereals and legumes, potatoes, vegetable crops, sugar beet, fruit and berry crops. The livestock sector has a dairy-meat direction. Among the agricultural products in the field crop production, the largest share belongs to potatoes and other vegetable crops (24,2%), and in the field of animal husbandry – to milk production (14,7%). The indices of crop and livestock production in households are somewhat higher (116.9 and 101,0%) than in agricultural enterprises (100,6% and 97,1%). The use of land resources by farms in Zhytomyr region is quite effective. This is evidenced by the agricultural product index, which is 105,2% compared to the previous year and the average indicator for Ukraine in 2017 (97,3%).